2008
DOI: 10.1177/1087057108318332
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Assay of G-Protein-Coupled Receptors Using Fluorescence Polarization

Abstract: A recently developed nanotechnology, the Integral Molecular lipoparticle, provides an essentially soluble cell-free system in which G-protein-coupled receptors (GPCRs) in their native conformations are concentrated within virus-like particles. As a result, the lipoparticle provides a means to overcome 2 common obstacles to the development of homogeneous, nonradioactive GPCR ligand-binding assays: membrane protein solubilization and low receptor density. The work reported here describes the first application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…FA assays have been developed for several GPCRs using fluorescently labeled ligands and cellular membranes containing the GPCR of interest. [5][6][7][8][9] In order to measure binding affinity, an FA assay does not require the separation of the receptor-bound fluorescent ligand from the unbound fluorescent ligand. The signal measured in the FA assay derives from the fact that a small, unbound fluorescently labeled ligand ("tracer") can rotate more quickly in solution relative to when bound to a larger receptor.…”
Section: Introductionmentioning
confidence: 99%
“…FA assays have been developed for several GPCRs using fluorescently labeled ligands and cellular membranes containing the GPCR of interest. [5][6][7][8][9] In order to measure binding affinity, an FA assay does not require the separation of the receptor-bound fluorescent ligand from the unbound fluorescent ligand. The signal measured in the FA assay derives from the fact that a small, unbound fluorescently labeled ligand ("tracer") can rotate more quickly in solution relative to when bound to a larger receptor.…”
Section: Introductionmentioning
confidence: 99%
“…This change, detected as fluorescence anisotropy, can be used as a measure of ligand binding and be monitored in real time. The FA method has been successfully 6 used for characterization of ligand binding to peptide receptors, such as chemokine CXC4 [23] and melanocortin MC4 [24], receptors of small molecules, such as muscarinic M1 [25] and serotoninergic 5-HT1A [26], and binding of nucleotides to G proteins [27]. It is important to mention here that the FA assay by nature is ratiometric, and signal can be detected only if the ratio of bound to free fluorescent ligand has significantly changed [28].…”
Section: Fluorescence -Fcs and Famentioning
confidence: 98%
“…This happens if the concentrations of receptor and ligand used are in a comparable range, and on the level of the dissociation constant of their interaction. Such a high level of receptor binding sites is usually difficult to achieve with natural tissues and therefore first attempts to implement this method have been performed with reconstituted systems [23]. The membranes of baculovirusinfected Sf9 cells demonstrated very reasonable anisotropy signals connected with ligand binding [24], while budded baculoviruses from these cells displaying GPCR on their surfaces are even more suitable targets for this type of assay [29].…”
Section: Fluorescence -Fcs and Famentioning
confidence: 99%
“…Due to the low expression in native systems, the poor quality of heterologous expression, difficult purification, and instability, studying these receptors in vitro is challenging (Allen, Ribeiro, Horuk, & Handel, 2009;Doré et al, 2011;Jones, Greene, Grygon, Doranz, & Brown, 2008;Langelaan, Ngweniform, & Rainey, 2011;McNeely, Naranjo, & Robinson, 2012;Wisedchaisri, Reichow, & Gonen, 2011). The previous purification of functional A 2 aR has shown that in order to retain its α-helical content and ligand-binding activity, the presence of cholesteryl hemisuccinate (CHS) is required when purified in dodecylmaltoside (DDM) (O'Malley et al, 2007).…”
Section: Membrane Mimetic Environmentsmentioning
confidence: 98%